2014
DOI: 10.2166/wp.2014.159
|View full text |Cite
|
Sign up to set email alerts
|

Water-conservation policies in perspective: insights from a Q-method study in Salta, Argentina

Abstract: Narratives and discourses on issues such as water management and other complex social-ecological systems respond partly to people's worldviews or social perspectives. Knowledge of these perspectives might help increase the rate of success of specific initiatives related to water conservation and could be an important tool to improve water governance. A study performed in the city of Salta, Argentina, revealed the existence of four social perspectives on issues related to water management. Perspectives were obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 48 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…Ormerod (2017) examined the subjective views of water stewards regarding the current planning discourse surrounding potable water reuse in the southwestern US. Iribarnegaray et al (2014) used Q methodology to show that the limited success of water policies in Salta (Argentina) was partly due to ignorance or disregard of users' social perspectives on water management.…”
Section: Q Methodologymentioning
confidence: 99%
“…Ormerod (2017) examined the subjective views of water stewards regarding the current planning discourse surrounding potable water reuse in the southwestern US. Iribarnegaray et al (2014) used Q methodology to show that the limited success of water policies in Salta (Argentina) was partly due to ignorance or disregard of users' social perspectives on water management.…”
Section: Q Methodologymentioning
confidence: 99%
“…The opinion of relevant local actors on the potential of a more open sustainability assessment method facilitated by online tools was solicited in open interviews. The selection of actors was based on a previous study we conducted in the city of Salta using Q methodology (see [19]), in which we identified four social perspectives on water and sanitation, namely: (a) Rights-based consumption advocates; (b) Proponents of market-based and technical water management; (c) Participatory governance advocates; and (d) State-led governance supporters. For the current study, we interviewed one actor for each social perspective identified [46][47][48].…”
Section: Virtual Interaction and Monitoring Spacesmentioning
confidence: 99%
“…However, the fact that results from these assessments are rarely incorporated into official decision-making processes has put sustainability indicators under scrutiny [18,19]. Particularly contentious issues in the use of these indicators are concerns with their transparency, openness, and democratic character as a result of the exceedingly technical approaches used that tend to preclude the participation of end users and other relevant stakeholders [17].…”
Section: Introductionmentioning
confidence: 99%
“…The results presented in this article focus on the qualitative data to develop rich descriptions of the subjectivity of the study participants: people who are particularly knowledgeable about urban water supply, water disposal, and water reuse options in the Southwest. In doing, this article contributes to the emerging field of "critical Q" scholarship (Sneegas 2019: 1), which integrates Q statistics with discourse analysis to understand how people align into shared worldviews (Cousins 2017a;Iribarnegaray et al 2014;Jepson et al 2012;Sneegas 2019;Ward 2013;Lehrer and Sneegas 2018;Nost et al 2019). The remainder of this article proceeds in five parts.…”
Section: Introductionmentioning
confidence: 99%